Cortical Substrate of Supraspinal Fatigue following Exhaustive Aerobic Exercise Localizes to a Large Cluster in the Anterior Premotor Cortex - Herath, Priyantha; Carmichael, Martin; Murphy, Angela; Bonilha, Leonardo; Newman-Norlund, Roger; Rorden, Chris; Davis, Mark (Frontiers in Neurology, 2017)
Strenuous exercise leads to a progressive reduction in the performance of voluntary physical exercise. This is due to a process described as fatigue and is defined as the failure to maintain the required or expected power output. While some of this is muscular in origin, fatigue may also be modulated by central mechanisms. Critically, previously reported fatigue-induced changes in cortical activity might actually reflect fMRI BOLD signal drift and/or neural habituation. In order to address this concern, we used a novel fMRI paradigm that enabled us to control for these potential confounds. In a counterbalanced within-subjects design, participants cycled until either lightly fatigued or until they reached a state of general exhaustion on two separate days. On each day, participants were scanned while contracting their hand before, during and after exercising their hand to exhaustion. We identify sites in the anterior ventral premotor cortex (aPMv), insula and postcentral gyrus as critical nodes in the brain network underlying supraspinal fatigue. Our data suggests that activity in the ipsilateral aPMv and adjacent areas in the premotor cortex correlates with both localized fatigue (fatigue specific hand contraction), and generalized, full-body exhaustive fatigue. Additionally, we show that the effects of BOLD signal drift can be modeled and effectively removed from studies that examine supraspinal fatigue. Once the loci of central fatigue are isolated in this way, treatments aimed at modulating activity in these premotor areas may reduce exercise-induced fatigue and perhaps also benefit various clinical conditions in which fatigue is a major symptom.